Place descriptions by landmarks. Issue 1 (2nd January 2017) - Zhou, Sha; Winter, Stephan; Vasardani, Maria; Zhou, Shunping
Abstract: Humans often describe places by landmarks in natural language. However, there is no appropriate digital representation of human concepts of place – a so far elusive concept – for use in information systems. This paper proposes and tests a formal model to capture the concept of place in human perception by transferring the concept of fingerprints from robotics: a place being characterized by the landmarks around it. For the purpose of realistically testing whether places can be described by fingerprints, an algorithm for computing places from fingerprints and, independently, an in situ survey to capture these places and their fingerprints were designed. The results indicate that the union of all locations with the same fingerprint characterizes a 'place' in human cognition.